Analisis Pengaruh Brand Image, Digital Marketing dan Direct Promotion terhadap Keputusan Pembeli - Haedar Alwi; Fathul Aminuddin Aziz (AHKAM, 2025)
The rapid advancement of digital technology has reshaped consumption patterns, with online shopping intensifying alongside the adoption of digital marketing. This study aims to analyze the effects of brand image, digital marketing, and direct promotion on consumer purchase decisions. Employing a qualitative methodology, it conducts a literature review drawing on journals, conference proceedings, books, and other relevant sources; the data are examined through descriptive-analytical comparison of prior studies and synthesis of extant findings. The main results indicate that brand image fosters trust through corporate, user, and product images; that digital marketing–based brand image serves as a primary vehicle to broaden reach, strengthen reputation, affirm quality, and shape brand experience; and that direct promotion effectively accelerates purchase decisions by creating urgency, a sense of personal relevance, and exclusivity. The study concludes that firms strategically integrating digital marketing–based brand image with well-targeted direct promotion can achieve competitive advantage by increasing sales while cultivating sustainable consumer loyalty. The contribution lies in offering consolidated evidence and practical guidance: businesses reliant on traditional marketing may consider transitioning toward digital marketing, while those already using marketplaces or digital platforms can leverage these insights to enhance brand image and direct promotion strategies.